Peran Orang Tua Dalam Mendampingi Anak Di Masa Pandemi Covid 19 - Aldi Hamsa; A. Arniyanti; Erna Kasim; Nurbaiti Nurbaiti (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction covid-19 is an infectious disease or virus that has never been known before. What role should parents play for their children during the Covid-19 pandemic? Objective explores how parents perceive their role during the covid-19 pandemic and accompany their children at home. Method this study explored quantitative evidence on the electronic databases of Pubmed, Garuda, and Google Scholar which resulted in 4 articles that became the main reference in the writing of this article. Results show that there are several roles parents have on their children such as guiding and motivating their children in doing their duties and always making sure their children always live clean and healthy and accompanying their children in using social media. Conclusion that the role of parents is very important and effective in the survival of children's learning to run like school in the covid-19 pandemic.